The Comparison between Right Hemisphere Dominance Students and Left One in Multiple Choice of English Test at the First Grade MAN 2 of Pamekasan - Syafrilia, Laily Komaril; Habibullah, Mosleh (PANYONARA: Journal of English Education, 2019)
The brain is divided into two nearly symmetrical halves, the right, and the left hemisphere. Left hemisphere handles all of analytical, logical matters, and language skill. On the contrary, art objects such as music, imagination, and colors handled by the right one. This research investigated whether there is a significant difference between right hemisphere dominance students and left one in multiple choice of English test. The researcher used ex-post facto research. The population is 294 of first-grade students. The simple random sampling technique used to select 40 students (20 right hemisphere dominance students and 20 left one). In gaining the data, three instruments have been used namely questionnaire, test, and documentation. The data were analyzed using independent t-test. The result revealed that there is a significant difference between right hemisphere dominance students and left one at the first grade MAN 2 of Pamekasan in multiple choice of English test (2.16 > 2.03; Significance level 5%, df = 35). Left brain dominance students are better in multiple choice of English test because language skill is placed on the left hemisphere. It also notified that differ hemisphere dominance students give different effect to the students? achievement in English testing, especially multiple-choice test.